Breast Cancer : Innovations in Research and Management - Veronesi, Umberto; Goldhirsch, Aron; Veronesi, Paolo; Gentilini, Oreste Davide; Leonardi, Maria Cristina (Springer International Publishing : Imprint: Springer, 2017)
This book provides the reader with up-to-date information on important advances in the understanding of breast cancer and innovative approaches to its management. Current and emerging perspectives on genetics, biology, and prevention are first discussed in depth, and individual sections are then devoted to pathology, imaging, oncological surgery, plastic and reconstructive surgery, medical oncology, and radiotherapy. In each case the focus is on the most recent progress and/or state of the art therapies and techniques. Further topics to receive detailed consideration include particular conditions requiring multidisciplinary approaches, the investigation of new drugs and immunological agents, lifestyle and psychological aspects, and biostatistics and informatics. The book will be an excellent reference for practitioners, interns and residents in medical oncology, oncologic surgery, radiotherapy, pathology, and human genetics, researchers, and advanced medical students.
Keywords: Medicine.; Human genetics.; Radiology.; Oncology.; Pathology.; Surgery.; elektronické knihy; electronic books